AKULTURASI PERKAWINAN SUKU SUNDA DAN SUKU JAWA DI DESA TANJUNG RATU KECAMATAN KATIBUNG KABUPATEN LAMPUNG SELATAN - Anis Marestiana; Ali Imron; Muhammad Basri (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2013)
Abstract: Acculturation is the mixture of two or more cultures gradually for a long time butwithout losing the characteristics of culture itself. Based on the formulation of the problem inthis study, namely "whatever form the result of acculturation marriage Sundanese and Javanesein the village of Tanjung Ratu district of South Lampung regency Katibung?" Therefore, thisstudy aimed to find out anything what form the results of acculturation marriage Sundanese andJavanese in the village of Tanjung Ratu Sub Katibung South Lampung regency. The methodused in this research is descriptive method. The technique of collecting data throughobservation, interviews and documentation, while the data analysis techniques using qualitativedata analysis techniques. Based on the analysis of the data shows the fact that the form of theresult of acculturation of marriage with Javanese and Sundanese are as follows: beginning withthe stage of choosing a mate is a mate anciently chosen by her parents, now children choosetheir own soul mate, the application stage the size of an application is planned by both the brideand groom's parents then determined by both parties and discussed, Panggih ceremony wasperformed, with little change, peoples settled after marriage also changed. So it can beconcluded that people living in the village of Tanjung Ratu Village Katibung District SouthLampung Regency, especially Sundanese and Javanese, have occurred acculturation, onethrough marriage.Keywords : Acculturation, Sundanese, Javanese